Antecedents Of Accountıng Knowledge Behavıor Analysıs And Recordıng Behavıor, Cultural Behavıor Accountıng And Revenue In MSMEs - Dokman Marulitua Situmorang; Andreas Aris Eko Mulyono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The aim of this research is to analyze the conditions regarding Accounting Knowledge Behavior, Accounting Recording Behavior, Cultural Behavior and Income in Micro, Small and Medium Enterprises in Tawangmangu District. The research method used is a qualitative research method. The results of the research are from the categories of type of business, gender, level of education, length of business, number of employees, income, that the accounting knowledge behavior of business actors still dominates in the basic and effective categories of accounting knowledge behavior with a portion of 75% of respondents of the 70 respondents taken. Based on the data collected from the categories of type of business, gender, level of education, length of business, number of employees, income, the accounting recording behavior of business actors has recorded but not according to genersally accepted accounting standards, most 90% of respondents noted this from the 70 respondents taken. Based on data collected from the categories of type of business, gender, level of education, length of business, number of employees, income, the accounting knowledge behavior of business actors when carrying out records and having simple accounting knowledge still has an income that is more than sufficient or above. above the expected average. Based on data collected from the categories of type of business, gender, level of education, length of business, number of employees, income, the cultural behavior of business actors still falls into the situation category, there are around 60% of the 70 respondents taken.